Fetal programming and epigenetic mechanisms in arterial hypertension. (July 2015) - Scherrer, Urs; Rimoldi, Stefano F.; Sartori, Claudio; Messerli, Franz H.; Rexhaj, Emrush
Abstract : Purpose of review: To provide an overview of available evidence of the potential role of epigenetics in the pathogenesis of hypertension and vascular dysfunction. Recent findings: Arterial hypertension is a highly heritable condition. Surprisingly, however, genetic variants only explain a tiny fraction of the phenotypic variation and the term 'missing heritability' has been coined to describe this phenomenon. Recent evidence suggests that phenotypic alteration that is unrelated to changes in DNA sequence (thereby escaping detection by classic genetic methodology) offers a potential explanation. Here, we present some basic information on epigenetics and review recent work consistent with the hypothesis of epigenetically induced arterial hypertension. Summary: New technologies that enable the rigorous assessment of epigenetic changes and their phenotypic consequences may provide the basis for explaining the missing heritability of arterial hypertension and offer new possibilities for treatment and/or prevention.